Cost-effectiveness of a medication event monitoring system for tuberculosis management in Morocco. - Jangmi Yang; Hae-Young Kim; Seup Park; Ilham Sentissi; Nathan Green; Byung Kwon Oh; Yujin Kim; Kyung Hyun Oh; Eunseong Paek; Young Joon Park; In-Hwan Oh; Seung Heon Lee (PLoS ONE)
Background Digital health technologies have been used to enhance adherence to TB medication, but the cost-effectiveness remains unclear. Methods We used the real data from the study conducted from April 2014 to December 2020 in Morocco using a smart pillbox with a web-based medication monitoring system, called Medication Event Monitoring Systems (MEMS). Cost-effectiveness was evaluated using a decision analysis model including Markov model for Multi-drug resistant (MDR) TB from the health system perspective. The primary outcome was the incremental cost-effectiveness ratio (ICER) per disability adjusted life-year (DALY) averted. Two-way sensitive analysis was done for the treatment success rate between MEMS and standard of care. Results The average total per-patient health system costs for treating a new TB patient under MEMS versus standard of care were $398.70 and $155.70, respectively. The MEMS strategy would reduce the number of drug-susceptible TB cases by 0.17 and MDR-TB cases by 0.01 per patient over five years. The ICER of MEMS was $434/DALY averted relative to standard of care, and was most susceptible to the TB treatment success rate of both strategies followed by the managing cost of MEMS. Conclusion MEMS is considered cost-effective for managing infectious active TB in Morocco.